Indigenous Knowledge & Intellectual Property: Negotiating the Spaces - Janke, Terri (The Australian Journal of Indigenous Education, 2008)
Abstract Indigenous knowledge is an integral part of Indigenous cultural heritage. Knowledge about land, seas, places and associated songs, stories, social practices, and oral traditions are important assets for Indigenous communities. Transmitted from generation to generation, Indigenous knowledge is constantly reinterpreted by Indigenous people. Through the existence and transmission of this intangible cultural heritage, Indigenous people are able to associate with a communal identity. The recording and fixing of Indigenous knowledge creates intellectual property (IP), rights of ownership to the material which the written or recorded in documents, sound recordings or films. Intellectual property rights allow the rights owners to control reproductions of the fixed form. IP laws are individual based and economic in nature. A concern for Indigenous people is that the ownership of the intellectual property which is generated from such processes, if often, not owned by them. The IP laws impact on the rights of traditional and Indigenous communities to their cultural heritage. This paper will explore the international developments, case studies, published protocols and policy initiatives concerning the recording, dissemination, digitisation, and commercial use of Indigenous knowledge.